Australian Acacia spp. extracts as natural food preservatives: Growth inhibition of food spoilage and food poisoning bacteria - Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: A. auriculiformis, A. disparrima and A. leptoloba are native Australian Acacia spp. which were used as both foods and medicines by the first Australians. Infusions and decoctions produced from leaves and bark have reputed antiseptic properties and were used traditionally to treat a variety of bacterial diseases. Despite this, Australian Acacia spp. solvent extractions have not been rigorously examined for antibacterial properties against food spoilage and food poisoning bacteria. Methods: The anti- microbial activity of A. auriculiformis, A. disparrima and A. leptoloba leaf extracts extractions was investigated by disc diffusion and growth time course assays against a panel of food spoilage and food poisoning bacteria. The growth inhibitory activity was quantified by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: A. auriculiformis, A. disparrima and A. leptoloba leaf extracts inhibited the growth of a wide range of bacterial species which cause food spoilage and food poisoning. A. auriculiformis extracts were generally more potent growth inhibitors than extracts prepared from the other species, although A. disparrima extracts were also potent inhibitors of bacterial growth. With few exceptions, the methanolic extracts were more potent growth inhibitors than the other solvent extractions. The methanolic A. auriculiformis leaf extract was a particularly potent inhibitor of K. pneumoniae and P. mirabilis, B. cereus and S. aureus growth, with MIC values of 97, 132, 178 and 109 µg/mL respectively. This extract was also a good inhibitor of A. faecalis, A. hydrophilia and S. newport growth (MIC’s <1000 µg/mL range). The A. disparrima extracts had a similar, albeit slightly less potent activity profiles. In contrast, the A. leptoloba leaf extracts were substantially less potent. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for use as natural food preservatives. Conclusions: The lack of toxicity of the A. auriculiformis, A. disparrima and A. leptoloba leaf extracts and their growth inhibitory bioactivity against a panel of food spoilage and food poisoning bacteria indicate their potential in the development of natural food preservatives.
Keywords: Acacia auriculiformis; Acacia disparrima; Acacia leptoloba; Fabaceae; Natural food preservatives; Australian plants; Antibacterial activity; Medicinal plants.